References of Folklore Malin Kundang - Yusi Susilawati; Dian Maryani (PROJECT (Professional Journal of English Education), 2019)
This research focuses on the use types of references (anaphoric, cataphoric, and exophoric reference) in the text of Malin Kundang folklore. The objectives of this research are to find out what types of reference used in folklore of Malin Kundang and how many types of reference for all paragraph in text of Malin Kundang folklore. The method that used in this research is descriptive qualitative method.. The researchers got the data from document analysis namely in the text of Malin Kundang folklore. The result from this research was the result from the tenth paragraph of the text of Malin Kundang folklore that have already done to analysis, there were 6 anaphoric references, 6 cataphoric references, and 3 exophoric references, so types of reference that many used in the text of Malin Kundang folklore were anaphoric and cataphoric references and the total of types of reference in the text of Malin Kundang are 15 types of references.